Tearing down inequalities in the healthcare system across Europe: the BEACON project - Koukoutzeli, Chrysanthi; Ferraris, Giulia; Coppini, Veronica; Ferrari, Maria Vittoria; Fragale, Elisa; Trapani, Dario; Minchella, Ida; Grasso, Roberto; Curigliano, Giuseppe; Pravettoni, Gabriella (Frontiers in Public Health, 2025)
Equity in healthcare remains a pressing issue in cancer care across the European Union. Although numerous European initiatives address prevention, early diagnosis, and treatment, significant disparities in access to innovative cancer therapies persist. Time-to-reimbursement for new anticancer drugs varies widely between member states, depending on national health policies, economic capacity, and healthcare infrastructure. These differences particularly affect countries in Central and Eastern Europe, where delays in reimbursement, limited access to clinical trials, and restricted availability of specialized care contribute to worse outcomes. This narrative review examines how disparities in reimbursement timelines and access to new cancer therapies may affect factors such as early detection, specialized treatment availability, clinical trial participation, and socioeconomic status. The discussion is framed within the BEACON project, a European Union-funded initiative under the EU4Health programme. BEACON brings together patients, healthcare providers, researchers, and policymakers to create a cross-border network for quality-assured diagnosis and treatment. Through its multilingual digital platform, the project fosters collaboration, supports health literacy, and enhances access to innovative cancer therapies, aiming to reduce inequities regardless of geographic or socioeconomic background.